EDUCATION, CLASS STRUGGLE, REVOLUTION. SUBJECTIVITY AND OBJECTIVITY IN THE THEORY OF KARL MARX - Viparelli, Irene (2011)
This article aims to investigate the relationship between education, class struggle and revolution based on Manifesto and the "historical texts" of Marx on the 1848 revolution. Initially, some confrontation will be shown fruitful by illuminating the basic features of the theoretical Marxian: rejecting both "objectivist" and "subjectivist" interpretations.  Marx’s theory of history turns out to be founded on two different times - linear and cyclical. These define a dialectical relationship between objectivity and subjectivity of history. Next, the same confrontation will be used to show that Marx represents the process in which the proletariat acquires a mature revolutionary consciousness. Far from considering it as "simple" development of proletarian class consciousness, Marx conceives this process as a more complex path, thus, it is implicated in all social classes. Finally, the last part is devoted to showing "empirically" this theoretical device in action: through the analysis of Marx on the development of class struggles in France, it will "almost" show the absolute centrality of the educational dimension in Marxist conception of history.